The protection effort of leopard cats (Prionailurus bengalensis Kerr, 1792) in the Upper Cisokan Pumped Storage, West Java, Indonesia - TEGUH HUSODO; ERRI NOVIAR MEGANTARA; ASEP ZAINAL MUTAQIN; DWI RUSTAM KENDARTO; INDRI WULANDARI; SYA SYA SHANIDA (Society for Indonesian Biodiversity, 2024)
Abstract. Husodo T, Megantara EN, Mutaqin AZ, Kendarto DR, Wulandari I, Shanida SS. 2024. The protection effort of leopard cats (Prionailurus bengalensis Kerr, 1792) in the Upper Cisokan Pumped Storage, West Java, Indonesia. Biodiversitas 25: 169-176. Humans develop various infrastructures to meet electricity needs so that it is to improve human welfare besides the increasing population. Hydropower development cannot be separated from land clearing, which damages and eliminates the habitats of wild animals, including leopard cats (Prionailurus bengalensis Kerr, 1792). Humans also cleared land as agricultural land to fulfill their needs. Fulfilling the needs of electricity and agriculture is necessary to improve human welfare. Besides, leopard cats need a suitable habitat to meet their needs. Therefore, protection effort is required to fulfill leopard cats' and humans' needs. The study aims to reveal the protection efforts in the Upper Cisokan Pumped Storage, West Java, Indonesia. A qualitative approach was applied through literature reviews. The protection effort of leopard cats was conducted through stakeholder participation in the UCPS area. As the initiator, Indonesia Hydropower Company (PT. PLN) involves various stakeholders related to the construction of the UCPS hydropower plant, including Perum Perhutani, contractors, and the local people. Indonesia Hydropower Company (PT. PLN) protects leopard cats by managing the impacts produced by the UCPS hydropower plant and biodiversity.